Vertical rotation parking using Radio Frequency Identification (RFID) based on Microcontroller - Reza Indie Fakhryan; Dwiprima Elvanny Myori (Journal of Industrial Automation and Electrical Engineering, 2025)
The vertical parking system is an innovative solution to optimize limited parking space, especially in urban areas. This research developed a prototype of a vertical rotation system based on Arduino Mega, which utilizes a DC motor as the rotational foundation of a gear chain mechanism to move the parking slot vertically. This system is also equipped with an ultrasonic sensor to detect the car's position, RFID as a user identification card, and a keypad to manually open the parking slot and car portal. For power stability, two step-down modules are used: one to supply the DC motor and another for the Arduino Mega, to avoid voltage surges and ensure the system runs optimally. The Arduino Mega acts as a control center that integrates all components and the system's working logic. Test results show that the system is able to quickly identify users, stop the slot rotation with high accuracy using an ultrasonic sensor, and maintain system stability through precise voltage regulation. This system offers an automated, efficient, and safe approach to vertical parking for users